The Effect of Planting Media Composition and NPK 16-16-16 Fertilizer Dosage on the Growth of Grafted Seedlings from Syzygium aqueum Burm.) - Prastika, Iftina Duta Prastika; Augustien K. , Nora; Utomo Pribadi, Didik (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Background: The success of water guava plant propagation is determined by proper cultivation and the availability of superior seeds. Water guava seedlings can be produced through generative and vegetative propagation or a combination. Splicing is joining two different parts of a plant into a whole unit and growing as one plant after tissue regeneration occurs in the graft scar. This study aims to determine the effect of the planting media type, the correct NPK fertilizer dose, and the interaction between the two on the growth of water guava seedlings resulting from shoot grafting. Methods: This research was conducted at the Horticultural Seed Development Unit, Pasuruan, East Java. This research took place from April to June 2023. Consisting of 2 factors, namely the composition of the soil planting media, soil: cow dung, soil: cow dung: rice husk charcoal, and the dose of NPK fertilizer, namely 16-16-16 1.3 grams, 2.7 grams, 4 grams. with two factors carried out, 1) the composition of the planting media (M) consisting of 3 levels and 2) the dose of NPK fertilizer 16-16-16 (D) consisting of 3 levels of treatment. The parameters observed were the time of emergence, number of shoots, length of shoots, number of leaves, height of grafted plants, and percentage of finished grafts. Results: The results showed that the treatment of the best results with the interaction of the composition of planting media soil: cow manure: husk charcoal with a dose of NPK fertilizer four g/plant at the age of 86 hssp on the shoot length parameter (5.86 cm). Single treatment, namely the composition of soil planting media: cow dung showed the best results in the parameter of the number of leaves 43 hssp (9,59), 57 hssp (13,22 strands), 73 hssp (21,30 strands) and 86 hssp (28,11 strands) and the percentage of finished grafts (87.80%), and the dose of NPK fertilizer 2,3 g/plant showed the best results in the parameter of shoot emergence time (9,96 hssp) and the dose of NPK fertilizer four g/plant on the shoot length parameter at the age of 43 hssp (0,83 cm). Conclusions: Using the composition of planting media and the dose of NPK fertilizer 16:16:16 can increase the yield of shoot grafts of water guava plants.